INFORMATION TECHNOLOGIES AND ECONOMIC GROWTH (Third Sector Social Economic Review, 2021)
Especially since the 1990s, there have been huge technological developments in information and communication areas. In this period, knowledge has become a serious production factor just like labor and capital. The importance of accessing the appropriate information in a timely manner causes the development and improvement of information technologies infrastructures. Being in every field of daily life, information and communication technologies lead to serious increases in productivity and consequently, these productivity increases positively affect economic growth. In this study, we examine the effects of information and communication technologies on economic growth for Turkey between 2001 and 2018. We use internet and mobile phone subscriptions and the volume of information technologies trade in the analysis. Applying Kalman Filter  in our model, we obtain the time varying coefficients for the variables.
Keywords: Economic Growth; Information Technologies; Kalman Filter